Dashing hopes?: the predictive accuracy of domestic abuse risk assessment by police - Turner, Emily (The British journal of criminology, 2019)
The Domestic Abuse, Stalking and Honour Based Violence (DASH) form is a standardized risk assessment implemented across most UK police forces. It is intended to facilitate an officer’s structured professional judgment about the risk a victim faces of serious harm at the hand of their abuser. Until now, it has been an open question whether this tool works in practice. Here, we present the largest scale European study, making the case that the risk assessment tool is underperforming. Each element of the DASH questionnaire is, at best, weakly predictive of revictimization. Officer risk predictions based on DASH are little better than random and a logistic regression model that predicts the same outcome using DASH only provides modest improvement in performance.